Engineering Mycorrhizal Symbioses to Alter Plant Metabolism and Improve Crop Health - French, Katherine E. (Frontiers in Microbiology, 2017)
Creating sustainable bioeconomies for the 21st century relies on optimizing the use of biological resources to improve agricultural productivity and create new products. Arbuscular mycorrhizae (phylum Glomeromycota) form symbiotic relationships with over 80% of vascular plants. In return for carbon, these fungi improve plant health and tolerance to environmental stress. This symbiosis is over 400 million years old and there are currently over 200 known arbuscular mycorrhizae, with dozens of new species described annually. Metagenomic sequencing of native soil communities, from species-rich meadows to mangroves, suggests biologically diverse habitats support a variety of mycorrhizal species with potential agricultural, medical, and biotechnological applications. This review looks at the effect of mycorrhizae on plant metabolism and how we can harness this symbiosis to improve crop health. I will first describe the mechanisms that underlie this symbiosis and what physiological, metabolic, and environmental factors trigger these plant-fungal relationships. These include mycorrhizal manipulation of host genetic expression, host mitochondrial and plastid proliferation, and increased production of terpenoids and jasmonic acid by the host plant. I will then discuss the effects of mycorrhizae on plant root and foliar secondary metabolism. I subsequently outline how mycorrhizae induce three key benefits in crops: defense against pathogen and herbivore attack, drought resistance, and heavy-metal tolerance. I conclude with an overview of current efforts to harness mycorrhizal diversity to improve crop health through customized inoculum. I argue future research should embrace synthetic biology to create mycorrhizal chasses with improved symbiotic abilities and potentially novel functions to improve plant health. As the effects of climate change and anthropogenic disturbance increase, the global diversity of arbuscular mycorrhizal fungi should be monitored and protected to ensure this important agricultural and biotechnological resource for the future.